Adapting a virtual manipulative-based instructional sequence to target maintenance. (May 2023) - Bassette, Laura; Bouck, Emily
Abstract: The ability to maintain mathematical skills learned is critical for students to successfully engage in advanced mathematics and promote independence in daily living skills. The purpose of this study was to evaluate the effectiveness of a graduated manipulative sequence consisting of virtual, representational, abstract, and an extended abstract phase (VRAEa) to teach various types of mathematical problems to three students with autism and mild intellectual disability using a multiple probe across behavior single case design. This study extended previous research on the virtual, representational, abstract sequence (VRA) to address deficiency in maintenance results through incorporating the extended abstract phase. The results indicate the intervention was effective, however, maintenance was variable. Implications for practice and ideas for future research to support the learning needs of students with developmental disabilities are discussed. Highlights: The instructional sequence improved mathematical performance. Performance during the maintenance phases was higher than baseline but variable. Prompting may be needed to teach maintenance of mathematical skills.